(untitled) (Research, Society and Development, 2020)
Objective: To propose reflections on the challenges of managers and health professionals in relation to the Coronavirus pandemic in Primary Care. Method: This is a reflective study of the evidence and documentation available on the coronavirus pandemic in primary care. Research was carried out on databases and websites of regulatory agencies. The text was organized into two themes: management and structural challenges in primary health care against coronavirus; Challenges to protect and value health professionals during the coronavirus pandemic. Results and Discussion: When faced with challenges, aspects such as quality assurance of outpatient care, given the scarcity of technology, the adequate structural quality so that professionals can act, including their safety, with the adequate supply of materials and training through education in the face of the new scenario become essential. Another challenge is in the context of current management, which in a way shakes the action of primary care, due to the deficit of professionals, which negatively impacts the current confrontation scenario. Conclusion: the study’s reflection refers to chronic factors in the management process, the deficit of professionals, the structural quality, as well as the supply of materials as factors that hinder the care process for users, corroborated by the population’s vulnerability, are challenges in this chaotic and exhausting scenario.